Sri Lanka - Public Sector Accounting and Auditing : A Comparison to International Standards - World Bank (Washington, DC, 2012)
This assessment of public sector accounting and auditing is generally meant to assist with the implementation o f more effective Public Financial Management (PFM) through better quality accounting and public audit processes in Sri Lanka. Following the introduction, and chapters on public sector accounting and auditing, Annex A explains the methodology used for the study. Annex B provides a summary of accounting and auditing standards referred to in this study. Annex C and D provide Sri Lanka accounting and auditing legislation, respectively. Lastly, Annex E includes a description of the benefits of accrual accounting.